Kajian Analisis Penyakit Pada Udang Vannamei (Litopenaeus Vananmei) Skala Intensif, Takalar, Sulawesi Selatan - Anwar, Kasful; Afandy, Alfa Astiana; Anggana Rarassari, Madyasta (JARI : Jurnal Akuakultur Rawa Indonesia, 2025)
Intensive brackish water whiteleg shrimp (Litopenaeus vananmei) cultivation has seen increasing production. This analysis study aimed to analyze the main diseases that attack whiteleg shrimp (Litopenaeus vananmei) intensively in Takalar Regency, South Sulawesi, and the distribution patterns of these diseases. The research method used a qualitative descriptive approach with data collection through literature studies, surveys, interviews, field observations, and laboratory studies. The study results indicated that the diseases intensively attack whiteleg shrimp in Takalar Regency were White Spot Syndrome Virus (WSSV), Enterocytozoon hepatopenaei (EHP), and Acute Hepatopancreatic Necrosis Disease (AHPND). The pattern of disease attacks occured more frequently during the transition season or the change from the dry season to the rainy season in Takalar Regency. This pattern of attacks occured when there is a drastic change in temperature that affects water quality parameters sucIh as pH, salinity, alkalinity, and ammonia levels. The spread of these shrimp diseases is transmitted horizontally in a cluster pattern. The results of the analysis and identification of these disease attacks are expected to be a reference for disease control strategies